Nurse-led compared to physician-led implant of cardiac monitors. (19th May 2022) - Steinhauer, B; Spicher, J; Aerschmann, S; Ambord, N; Bartkowiak, J; Servatius, H; Noti, F; Seiler, J; Baldinger, S; Haeberlin, A; Madaffari, A; Tanner, H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Implantation of an implantable cardiac monitor (ICM) is a simple and straightforward procedure. However, with a growing demand for such implants, workload significantly increases. In January 2020, we established a completely nurse-led ICM implantation service (N-IMPLANT) with a standard operating procedure. Purpose: The present study aimed to analyze the safety, efficacy, and patient satisfaction of N-IMPLANT compared to implantation of ICMs by a physician (P-IMPLANT). Method: Consenting patients implanted with an ICM were included in a prospective registry, which collects patient characteristics, procedural and remote monitoring data. All patients were followed-up by phone interview four weeks after ICM implantation and a standardized questionnaire was completed. Results: Of 321 patients implanted with an ICM (median age 67 years; 33% women), 189 (59%) were N-IMPLANT. Significantly more N-IMPLANT were performed in the outpatient clinic compared to P-IMPLANT (94% vs. 10%; p<0.001). For wound closure, N-IMPLANT used wound glue in 65 (34%) and a single subcutaneous stitch in 124 patients (66%). Two N-IMPLANT patients experienced vaso-vagal reaction during implantation, whereas no adverse events occurred during P-IMPLANT (p=0.51). Two-hundred and fifty-two patients (79%) completed the questionnaire. We found no difference between N-IMPLANT and P-IMPLANT regarding pain after implant, analgesic use, wound closure after 2 weeks and presence and size of patient reported hematoma (see Table). Duration of pain was longer after P-IMPLANT. All N-IMPLANT patients indicated to be satisfied with the implant procedure. Three patients were dissatisfied with P-IMPLANT for the following reasons: ongoing pain at implant site; discomfort at implant site; and too numerous people present during the implant procedure. In three N-IMPLANT (2%) the ICM was explanted prematurely. The reasons for explantation were infection (with reimplantation of another ICM), discomfort at implant site and attempt to avoid interferences during magnetic resonance tomography in one patient each. One P-IMPLANT (1%) was explanted prematurely because of ICM malfunction. Conclusion: Nurse-led implantation of cardiac monitors is effective without compromising patient safety and has excellent patient satisfaction. N-IMPLANT is a suitable model to reduce the workload of physicians.